2020
DOI: 10.3390/genes11040425
|View full text |Cite
|
Sign up to set email alerts
|

Methylation Analysis of CpG Islands in Pineapple SERK1 Promoter

Abstract: Somatic embryogenesis (SE) is a more rapid and controllable method for plant propagation than traditional breeding methods. However, it often suffers from limited efficiency. SERK1 promotes SE in several plants, including pineapple (Ananas comosus L.). We investigate the embryonic cell-specific transcriptional regulation of AcSERK1 by methylation analysis of CpG islands in AcSERK1 regulatory sequences. This revealed differences in the methylation status of CpG islands between embryonic callus and non-embryonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…At 60% FC, PP2C and PAL which have CpG islands in their promoter region showed lower levels of expression than HSP70 and RH25 which do not contain CpG island. A recent study on pineapple suggested that, DNA methylation at CpG islands in the promoter regions of a gene promoting somatic embryogenesis, SERK1 represses its expression (Luan et al ., 2020). Another study on transgenic flax crop showed that the gene chalcone synthase was more accessible to DNA methylation when located within CpG islands and the expression of the gene depended on the methylation status in these regions (Dzialo et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…At 60% FC, PP2C and PAL which have CpG islands in their promoter region showed lower levels of expression than HSP70 and RH25 which do not contain CpG island. A recent study on pineapple suggested that, DNA methylation at CpG islands in the promoter regions of a gene promoting somatic embryogenesis, SERK1 represses its expression (Luan et al ., 2020). Another study on transgenic flax crop showed that the gene chalcone synthase was more accessible to DNA methylation when located within CpG islands and the expression of the gene depended on the methylation status in these regions (Dzialo et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The gene of an expressed protein (Ananas β-Actin) served as internal control. This was previously proposed as reference gene (Luan et al, 2020).…”
Section: Quantitative Real-time Pcr (Qrt-pcr)mentioning
confidence: 99%
“…[2] It is a self-sterile plant, and the propagation methods widely used is from suckers. [3 The traditional propagation of suckers facilitate the production of pineapple but has enormous disadvantages, such as low rate of multiplication, long period of production, high variation in size, weight and age, and non-uniform vegetative cycle. [3 -4] Therefore, tissue culture have become an alternative methods for mass production of healthy pineapple planting material with homogeneity of morphotypes.…”
Section: -Introductionmentioning
confidence: 99%